Kebijakan Wajib Militer Universal Norwegia Sebagai Implementasi Nyata Kesetaraan Gender - Vera Tesalonika Manik; Reni Windiani; Satwika Paramasatya (Journal of International Relations, 2022)
Norway is one of the countries that is well-known for its achievements in gender equality. Alongside that, Norway is a country that implements the policy of Military Conscription for its defense. In 2013, Norway Parliament, namely Storting, adopted the Universal Conscription Policy. Through this policy, women consequently have the same responsibilities as men in joining the military service. In addition to that, there is no difference in the requirements set by the Norwegian Government for men and women in the Universal Conscription Policy. This article thus tries to explain the reasoning behind the establishment of the Universal Conscription Policy in Norway. The analysis is conducted through the perspective of feminism normative theory with qualitative research methods, specifically with discourse analysis. The result of this article shows that the formation of the Universal Conscription Policy in Norway is the impact of discursive practices carried out by the Norwegian Government related to the understanding of gender equality.